Therapeutic implications of the fertility of the hydratic cyst in the different states evolutions of human hydatidosis - Alvarez Gabrielli, Carmelo; Perdomo, Roberto (Cirugía del Uruguay, 1994)
Fertility was determined in different evolutives stages of human hydatic cyst (HC). The highest vitality was found in hialine cyst, in most of the multivesicular cysts and in daugther cyst of partially degenerated cysts. There was no fertility in degenerated cysts ar in mastics. The presence of bife and suppuration was seen in dead cysts, except when the daugther cyst remained sound. Oissemination risks were considered highin ultrasound-guided taps, as well as laparoscopic surgery, even in sma/1 hyaline cyst. Pharmacological treatment would be useful only in certain chosen fertile cysts.